Design and Construction of Speed Control System of Brushless Direct Current Motor 350 Watt Type 120 and 60 Degrees on Prototype Electric Vehicles using Configuration Six-Step Commutation - Muhammad Andre Budi Leksono; Triwahju Hardianto; RB Moch. Gozali (Department of Electrical Engineering, Faculty of Engineering, Universitas Negeri Surabaya, 2022)
In the world of electric cars, the motor speed control system plays an important role in the design of an electric car. A vehicle will run if the control or control of a drive in the form of a motor runs stably and has little energy consumption. One way to achieve this stability is by understanding the commutation accuracy of each motor used. The purpose of this final project is to design a brushless direct current motor speed control system of type 120 and 60 degrees using the Six-Step Commutation configuration.